An Ecocritique of Postmodern Culture in Oryx and Crake - Kevser Ateş (Journal of Literature and Humanities)
In this dystopian world where technology has brought about social degradation, Margaret Atwood interrogates how humans and animals transform into commodities in a techno-cultural and hyperreal society. The novel seems to be a warning about the possible catastrophic results of our wrongdoings in the near future with the profit-seeking and powerful multinational corporations recklessly controlling and misusing science and technology for their purposes. It compares the life of an emerging new community comprised of humanoids called Crakers, non-violent, innocent, and peaceful creatures, in a post-apocalyptic world, and the world before the apocalypse presented by the memories of Jimmy, initially believed to be the only human being who survived after a worldwide pandemic, or Snowman- his post-apocalyptic name used by Crakers. Atwood posits the world of Crakers as a place where there is no trace of irresponsible, and reckless damaging actions of the previous world as Crake, the young, genius scientist who has bioengineered them, has made them free of all the devastating, faulty human characteristics such as racism, social order, land control and fear of death. On the other hand, in the pre-epidemic world, Atwood skillfully and vividly designs a world of consumer and pleasure-seeking corporate culture lacking ethical and ecological values. This chapter sets out to shed light on contemporary problems through the examples in the novel in which despite securing scientific and technological possibilities, people do not seem to achieve social and environmental progress.